(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Catalysts and catalytic promoters played a very important role not only in the chemical process but also in all biochemical processes. The term “Catalysis” is known for its importance in process efficiency and product selectivity, starting from small-scale reactions to large scale industrial processes. Currently, catalysts are extensively exploited in all areas of chemical industries including petroleum, petrochemical fertilizers, polymers, fine chemicals, drugs and drug intermediates. Therefore, it is considered that the importance of catalysts in modern chemical industry is unaccountable and inevitable. Because, the catalytic materials has a tremendous economic impact and in turn reflected in growth of the concerned industrieslaboratories.